THE EFFECT OF VEHICLES INTENSITY IN SUMBERSARI JEMBER REGENCY - Eva Kurnia Sari; Dinda Ayu Pramesty (Department of Geography Education, University of Jember, 2018)
The main problem is vehicles very much owned by the public of Indonesia. One of transportation that is used population usefulness as a tool for mobility to a place that will be addressed, from rural to urban areas or vice versa. Community needs more triggers the movement of people from one place to another. Highway average - average be passed by a motorcycle and a car. Geography and transport have a very close relationship. The purpose of this study was to analyze the density of the vehicle in the sumbersari area of Kabupaten Jember. The method used is a survey using a sample area. The results showed that vehicle density most often occurs in the morning and evening. Keywords: mobility, effective today, the volume of vehicles References Alhani et al. 2016 Suburban, IN, Pontianak, Case Road, and Sungai Raya.